Segmental pulmonary veno-occlusive disease secondary to lung cancer. Issue 4 (24th March 2005) - Ibrahim, N B N; Burnley, H; Gaber, K A; Ormerod, L J; Addis, B; Capron, F; McGavin, C R
Abstract : This report describes two cases of segmental pulmonary vein occlusion secondary to lung malignancy in which lung biopsies showed histological features of veno-occlusive disease. These are the first cases to be reported in the literature in which such lung parenchymal histological changes are described in association with lung malignancy.